The importance of smartphone's usage among Malaysian undergraduates - Mohd Mothar, Noor Mayudia; Abu Hassan, Musa; Hassan, Md. Salleh; Osman, Mohd Nizam (International Organization Of Scientific Research, 2013)
Since its debut, smartphone had been steadily replacing the existence of the conventional mobile phone. The change was well accepted and proven by the smartphones’ surging sales throughout these years. Furthermore, smartphone become a necessity to universities students. Apart from allowing them to socially interact with others, it also can entertain as well as provide platform to search for information. Nowadays the smartphone could also be use to channel its owners’ personality. This research implies that pattern of smartphone’s usage was categories into four typologies that includes Information, Personal Identity, Integration and Social Interaction, and Entertainment. With data from 385 undergraduate students from public and private university in Malaysia, the researcher was able to conclude that the usage for personal identity was important to them. The results were able to clarify the students’ interest over their smartphone and confirm its popularity among youngsters.